ANALISIS PENGARUH KAPABILITAS PENGINDERAAN PASAR, INOVASI PRODUK, DAN JEJARING PEMASARAN TERHADAP KEUNGGULAN BERSAING PADA KINERJA PEMASARAN EKSPOR - Fauzi, Devita Ekky; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
This research was conducted at the company in Jepara furniture exporter that exports to many countries in the world. Nowadays many exporters are racing to meet the wishes of the world market. This study aims to analyze and provide empirical evidence about whether the market sensing capabilities, product innovation, and marketing networks affect the competitive advantage on export marketing performance.Samples were furniture exporters are active in the town of Jepara furniture exports to various countries in the world by using quantitative analysis method, by using the test reliability and validity, the classical assumption, hypothesis testing, coefficient determinant and SEM analysis with AMOS 7.0 program.The results showed that the market sensing capability and product innovation positive effect on competitive advantage and competitive advantage positive effect on network marketing and export marketing performance and capability of sensing market, product innovation, competitive advantage, marketing networking positive effect on export marketing performance. In model 1, the market-sensing capability provides the greatest influence on the competitive advantage of 0.412. In model 2, the competitive advantage of providing the greatest influence on export marketing performance of 0.263.